2004
DOI: 10.1161/01.cir.0000141576.39579.23
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Endothelial-Cell Caveolin-1α/Raft Scaffolding During Development of Monocrotaline-Induced Pulmonary Hypertension

Abstract: Background-In the monocrotaline (MCT)-treated rat, there is marked stimulation of DNA synthesis and megalocytosis of pulmonary arterial endothelial cells (PAECs) within 3 to 4 days, followed by pulmonary hypertension (PH) 10 to 14 days later. Growing evidence implicates caveolin-1 (cav-1) in plasma membrane rafts as a negative regulator of promitogenic signaling. We have investigated the integrity and function of endothelial cell-selective cav-1␣/raft signaling in MCT-induced PH. Methods and Results-Although P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
193
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(214 citation statements)
references
References 37 publications
20
193
1
Order By: Relevance
“…This reciprocal relationship between cav-1 downregulation and PY-STAT3 activation in PAH in the rat/MCT model was later confirmed by Jasmin and colleagues (19). That the increase in PY-STAT3 levels was seen before the onset of PAH in MCT-treated rats (19,24) and that the introduction of a cav-1 scaffolding domain peptide blocked PY-STAT3 hyperactivation and ameliorated MCT-induced PAH (19) indicated that STAT3 played a role in the initiation of PAH, at least in this animal model. Moreover, Park and colleagues (33) reported the hyperactivation of PY-STAT3 in lungs of cav-1 Ϫ/Ϫ mice, which spontaneously developed PAH.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…This reciprocal relationship between cav-1 downregulation and PY-STAT3 activation in PAH in the rat/MCT model was later confirmed by Jasmin and colleagues (19). That the increase in PY-STAT3 levels was seen before the onset of PAH in MCT-treated rats (19,24) and that the introduction of a cav-1 scaffolding domain peptide blocked PY-STAT3 hyperactivation and ameliorated MCT-induced PAH (19) indicated that STAT3 played a role in the initiation of PAH, at least in this animal model. Moreover, Park and colleagues (33) reported the hyperactivation of PY-STAT3 in lungs of cav-1 Ϫ/Ϫ mice, which spontaneously developed PAH.…”
mentioning
confidence: 69%
“…24). Close examination of individual cells in vivo showed that the specific endothelial cells that had a loss of cav-1 expression were the same cells with hyperactivation of PY-STAT3 and increased DNA synthesis (24). This reciprocal relationship between cav-1 downregulation and PY-STAT3 activation in PAH in the rat/MCT model was later confirmed by Jasmin and colleagues (19).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, at 1 wk post-MCT before the development of PH, progressive activation of PY-STAT3 and increased expression of Bcl-xL occur (48,78). At 2 wk post-MCT, there is evidence of PH and right ventricular hypertrophy; only 26 Ϯ 3% of the arteries exhibit the presence of endothelial caveolin-1 compared with the controls with intact endothelial caveolin-1 in 100% of arteries (49).…”
Section: Disruption Of Ec Membranementioning
confidence: 99%
“…The expression of the endothelial caveolin-1 was reduced in these cases. In the MCT model, progressive loss of endothelial caveolin-1 and the activation of proliferative and antiapoptotic pathways occur before the onset of PH (48,78). The rescue of caveolin-1 inhibits the proliferative pathways (PY-STAT3, cyclin D1 and D3) and attenuates PH (47,60).…”
Section: Disruption Of Ec Membranementioning
confidence: 99%